National disability insurance scheme access: What evidence do you need to provide for psychosocial disability?. (April 2023) - Shelby-James, Tania; Duncan, Amy; Rattray, Megan; Reed, Richard
Objectives: The National Disability Insurance Scheme (NDIS) was introduced in 2013 and offered a new way of providing support to people with permanent and significant disabilities. Despite pilot testing, implementation of the scheme has been challenging, particularly for people with a disability arising from a mental health condition. In 2019, to address the challenge of accessing the NDIS, researchers from Flinders University worked with the National Disability Insurance Agency (NDIA) to develop a streamlined access process for psychosocial disability. The aim of this paper is to provide guidance on the evidence required to demonstrate that a person has a significant and persistent psychosocial disability to access the NDIS. Conclusion: Providing evidence for a psychosocial disability requires knowledge of how to address the disability requirements. The Evidence of Psychosocial Disability (EPD) form has been designed to address these requirements and offers guidance on the evidence that should be provided. A range of resources to accompany the EPD form are freely available online. These resources address a significant knowledge gap that currently exists with the implementation of the NDIS.